Validitas dan Reliabilitas Ujian Keahlian Pelaut Bahasa Inggris Maritim - Gumay, Andesvan; Nurika, Yohanna; Herningsih, Siwi Woro; Magdalena, Susiarni (JOEAI (Journal of Education and Instruction), 2022)
The purpose of this research is to determine the validity and reliability of the Maritime English proficiency test organized by PUKP (Seafarer Expertise Exam) 02 Banten and its surroundings. Research method was used is descriptive analysis because it aims to explain the level of difficulty, discriminatory power, as well as the validity and reliability of exam questions for 3rd grade students at the Maritime School. The results showed that there were 43 valid exam questions in the Nautical department or about 71.66% of the total questions, with a correlation value greater than Rtable 0.1071 with a significance level of 5%. As for the Engineering department, there are 41 valid exam questions or 68.33% of the total questions, with a correlation value greater than Rtable 0.2483 with a significance level of 5%. For the reliability of the test questions in the Nautical department of 0.5968 and the Engineering department 0.6789 with an interval between 0.40 to 0.70 with moderated interpretation. Therefore, it can be concluded that the Maritime English exam questions used are quite valid and reliable. Keywords: validity, reliability, proficiency test, maritime English.